The influence of internet use frequency, family atmosphere, and academic performance on adolescent depression: Based on the chain mediating effect of self-adjustment and campus deviant behavior - Jiang, Mao-min; Wang, De-wen; Wu, Zheng-yu; Gao, Kai; Guo, Pei-pei; Kong, Yang (Frontiers in Psychology, 2022)
Depression has become a prominent psychological problem among young people. The purpose of this study was to investigate the potential relationship between the frequency of Internet use, family atmosphere, academic performance, self-adjustment, campus deviant behavior and depressive symptoms among adolescents. Based on the survey data of the fifth wave (2017~2018) and the sixth wave (2019~2020) of the China Family Panel Studies (CFPS), this study used LISREL8.8 software to analyze 1577 10~15 data on adolescents. In this study, The mean score of self-adjustment was 42.40 (SD=6.79), the mean score of campus deviant behavior was 12.59 (SD=4.00), the mean score of depressive symptoms in 2018 was 11.88 (SD=3.04), and the mean score of depressive symptoms in 2020 was 7.64 (SD=2.20). Secondly, the frequency of Internet use had no direct effect on the depressive symptoms of adolescents, family atmosphere was negatively correlated with depressive symptoms (p<0.005), and academic performance was positively correlated with depressive symptoms (p<0.005). Depressive symptoms in 2020 had a direct effect (β=0.37, p<0.001), and also had a negative effect on depressive symptoms in 2020, with a total effect of -0.07 (p<0.001); self-adjustment had no direct effect on depressive symptoms in adolescents in 2018, However, the total effect was -0.14 (p<0.001), which had a significant positive effect on 2020 depressive symptoms, and the total effect was 0.18 (p<0.001), and self-adjustment had a significant negative effect on adolescent campus deviant behavior (β= -0.38, p<0.001); in addition, the frequency of Internet use, family atmosphere, and academic performance all had indirect effects on adolescents' 2020 depressive symptoms, with total effects of -0.60, 0.01, and 0.02 (p<0.001), respectively. This study also found depressive symptoms in adolescents have a certain persistence in time. Based on this study, it is necessary to pay more attention to the depression of adolescents, strengthen the training of self-adjustment, improve the anti-frustration ability and psychological resilience, and reduce the campus deviant behavior of adolescents. It is recommended to try to start from emotional self-adjustment to promote the personality health of adolescents.